ANALISIS PENGARUH PENGANGGURAN TERBUKA, KEMISKINAN DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT TAHUN 2013-2024 - Al Muslimah; Rosita Rosita; Ahmad Suhendri (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the effect of the open unemployment rate, poverty, and the Human Development Index (HDI) on economic growth in West Nusa Tenggara Province during the 2013–2024 period. The data used are secondary time series data obtained from the Central Bureau of Statistics. The analytical method employed is multiple linear regression, preceded by classical assumption tests including multicollinearity, heteroskedasticity, autocorrelation, and linearity. The results show that partially (t-test) and simultaneously (F-test), the variables of open unemploymeoverty, and HDI do not have a significant effect on economic growth. In terms of direction, open unemployment and poverty exhibit a positive relationship, while HDI shows a negative relationship; however, all variables are statistically insignificant. The Adjusted R-squared value of 0.108 indicates that the model explains only 10.8% of the variation in economic growth, while the remaining proportion is influenced by other factors outside the model. In conclusion, economic growth in West Nusa Tenggara Province during the study period is not significantly affected by open unemployment, poverty, and HDI. This suggests that regional economic growth is more influenced by other structural and macroeconomic factors, such as investment, government expenditure, and the dynamics of leading sectors.